2005
DOI: 10.1002/cncr.20884
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of cytologic atypia in repeat nipple duct lavage

Abstract: Background Farm operators experience exposure to high noise and high prevalence of noise‐induced hearing loss, but use of hearing protection in this worker group is low. The purpose of this study was to test a brief intervention to increase farm operators' use of hearing protection. Methods In this one‐group pre‐ and post‐test study, a random sample of 32 members of a farmers' organization was supplied a variety of hearing protectors. Participants received an assortment of hearing protectors by mail with manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
(42 reference statements)
5
20
0
Order By: Relevance
“…Cytologic reproducibility was low for benign, mildly atypical, and markedly atypical cells. In a study examining the reproducibility of the diagnosis of atypia using Thin Prep (Cytyc) rather than cytospin, the results were similar to the present study (2). Poor reproducibility of atypia may contribute to higher false-positive or false-negative tests; as seen in our study, a cytologic diagnosis of atypical cells can lead to additional tests and anxiety despite communication to both the physician and study participant about the lack of scientific data associating atypical cells and breast cancer development.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Cytologic reproducibility was low for benign, mildly atypical, and markedly atypical cells. In a study examining the reproducibility of the diagnosis of atypia using Thin Prep (Cytyc) rather than cytospin, the results were similar to the present study (2). Poor reproducibility of atypia may contribute to higher false-positive or false-negative tests; as seen in our study, a cytologic diagnosis of atypical cells can lead to additional tests and anxiety despite communication to both the physician and study participant about the lack of scientific data associating atypical cells and breast cancer development.…”
Section: Discussionsupporting
confidence: 87%
“…The reported prevalence of markedly and mildly atypical cells as well as the percentage of ICMD in premenopausal women in this study was similar to those studies that have evaluated similar populations (1,2). Overall variability in cytology and cellular yield between ductal lavage studies could be due to differences in patient population characteristics, specimen processing, or individual variations in technique.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, the process has been hampered by difficulties in sampling of nipple duct fluid as well as the lack of predictive capability by cytologic analysis. 68 In one series, the methylation status of 11 tumor suppressor genes from ductal epithelial cells predicted sporadic and hereditary cancer with an accuracy approaching 90%. 69 Importantly, it appears that methylation changes are apparent in the ductal epithelial cells obtained from nipple duct fluid regardless of the location of the primary breast tumor.…”
Section: Methylation Changes As a Biomarkermentioning
confidence: 99%
“…A recent study by Johnson-Maddux et al indicated that sampling and/or interpretive variance with ductal lavage specimens is not trivial. Only 48% of women producing atypical ductal lavage samples on the first attempt were found to have atypical samples on a subsequent attempt (15). Thus, the combination of sampling and interpretive variance with lavage is unlikely to be less than for RPFNA (18,19).…”
mentioning
confidence: 99%